TACTICS OF SURGICAL TREATMENT FOR RECTAL PROLAPSE - Rustamov, A.E.; Navruzov, B.S.; Egamberdieva, E.X.; Babajonov, A.B.; Eshmurodova, D.B.; Eshmurodov, Sh.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To study the results of surgical treatment of the patients with rectal prolapse. Material and Methods: During the period from 2003 until 2018, at the Coloproctology department of 1st Clinical hospital of the Ministry of health of the Republic of Uzbekistan 426 patients were operated with the diagnosis of rectal prolapse, the average age of the patients was 45,2±3,8 y.o. Analysis of the results of treatment revealed the absence of postoperative mortality. Relapse was observed in 4 (0.94%) cases, however, the number of patients with constipation decreased from 28% who noted constipation prior to surgery, to 4% after it. Long-term results in all patients are satisfactory - low recurrence rate and acceptable anal sphincter function. On large material, it is confirmed, that surgery with prolapse of the rectum should be not only radical, but also reconstructive – restorative. Conclusions: on a large material it was shown that surgery in case of prolapse of the rectum should be not only radical, but also reconstructive.